Topographical Mapping of the cardiac autonomic innervation for selective cardiac neuromodulation in pigs and rabbits using MicroCT. (10th June 2022) - Kronsteiner, B; Zopf, L; Heimel, P; Oberoi, G; Kramer, A-M; Slezak, P; Reissig, L; Geyer, S; Weninger, WJ; Podesser, BK; Kiss, A; Moscato, F
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): Horizon 2020- EU H2020-EU.1.2.2. - FET Proactive "NeuHeart" Nr. 824071 Background & Introduction: In recent years, Vagus Nerve Stimulation (VNS) has proved to be a potential therapeutic approach for the treatment of cardiovascular diseases, such as Heart Failure or atrial fibrillation [1]. However, the lack of specific anatomical knowledge of the cervical VN [2, 3] and thus, of the cardiac autonomic innervation aggravates the side effects of unselective cervical VNS. Purpose: The goal of this study was to investigate the cardiac vagus nerve branches for selective cardiac VNS stimulation using micro-computed tomography (µCT) and 3D renderings. Methods: Vagus nerve specimens (n= 11 pig nerves, n= 5 rabbit nerves) were harvested from the nodose ganglion down to the cardiac branches in domestic pigs and New Zealand White rabbits on both sides, and the cardiac autonomic innervation was mapped µCT and 3D renderings. Results: Our results provide anatomical and topographical key features on the cervical and cardiac autonomic innervation including course of the cardiac branch, cardiac branching patterns, fascicle number, and size of the autonomic nerves. We also compared these aforementioned anatomical parameters between pigs and rabbits and highlighted key anatomical differences among individuals within pigs. In pigs, the cardiac branches were partly composed of both nerves even when they branched off the VN whereas in rabbits, the two nerves were completely separated and the cardiac branch was solely parasympathetic. Finally, we generated a 3D model of various parts of the VN specimen and compared them to images of the native nerves taken during VN dissection surgery. Conclusions: Here we present an imaging approach to map the anatomy and topography of the cardiac Vagus Nerve for selective stimulation of cardiac VN branches. We also characterized the morphology of the VN, the sympathetic trunk (ST), and the cardiac branch (CB) at the level of the cardiac branching point to highlight the complex interplay between the nerves. Our data provide one possible reason for unwanted side effects of cervical VNS. However, future studies are required to broaden the knowledge in this specific research field of selective cardiac VNS.